Bolus administration of tranexamic acid with a maintenance dose via infusion and strict blood pressure control for non-traumatic intracerebral hemorrhages - Arumugam, Ananda (2014)

(untitled)
Introduction Spontaneous intracerebral hemorrhages (ICH) account for 10–15% of all strokes with an incidence of 10–30 cases per 100,000 people/year, and their incidences are expected to double in the next 30 years. Mortality and morbidity associated with ICHs is still high. Until recently, there were no effective evidence-based treatments for acute ICH. ICH growth remains an important predictor of patient outcomes. Tranexamic acid (TXA), an anti-fibrinolytic drug, is known to reduce hemorrhaging in other conditions. The purpose of this study was to assess the effect of TXA compared to a placebo on the growth of hematomas in patients with spontaneous ICH. Methodology A single-blinded randomized placebo-controlled trial was conducted using TXA (intravenous 1 g bolus followed by an infusion of TXA at 1g/h for 8 h) in acute (<8 h) cases of primary ICH. Strict blood pressure control (target systolic blood pressure [SBP], 140–160 mmHg) was achieved using labetalol infusion. A repeat brain computed tomography (CT) was performed in the next 24 h to reassess the hematoma growth. The primary objective was to test the effect of TXA on hematoma growth. The secondary objective was to test the feasibility, tolerability, and adverse events of TXA in cases of primary ICH. Results Thirty patients were recruited between September 2012 and October 2013. The patients’ mean age was 49 with male predominance (70%). The baseline SBP was 150 mmHg), mean Glasgow Coma Scale score was 13–15/15), and median time from stroke to the 1st CT scan was 5.5 h. The hematoma locations were as follows: internal capsule, 80%; thalamus, 13.3%; and head of caudate, 6.66%. The mean total hemorrhage growth was 0.16 mL and 3.07 mL in the treatment and placebo groups, respectively. Statistical analysis showed a reduction in the total hemorrhage growth in the TXA group in comparison to the control (p < 0.05). Conclusions Patients who present with spontaneous ICH secondary to uncontrolled hypertension should be treated with a combination of a bolus administration of TXA (1 g) and a maintenance dose via infusion (1 g/8 h) with strict blood pressure control, rather than blood pressure control alone. However, a double-blinded randomized study with multicenter involvement is needed for further evaluation of the significance of this finding.